Mediation model of job satisfaction on employee performance the tebing tinggi city credit union - Situmorang, Anderson Hasiholan; Ananda, Putri; Siregar, Aisyah; Cahyadi, Lukieto (Jurnal Mantik, 2024)
The purpose of this research is to determine and analyze job satisfaction in mediating the influence of the work environment, career development and competency on employee performance at New Life Credit Union, Tebing Tinggi City. The sample in this study used a saturated sample, where the entire population was sampled. The sample in this research was 35 employees. Data collection techniques in this research used a questionnaire, while the data was analyzed. The technique in this research uses quantitative data analysis methods, with SEM-PLS statistical analysis. Data processing in this research uses SmartPLS 3.0. Software program The results of this research prove that the work environment has no significant effect on performance, the work environment directly has a significant effect on job satisfaction, career development has no significant effect on performance, career development directly has a significant effect on job satisfaction, career development has a direct effect significant effect on performance, competency has no effect on performance, competence has a significant effect on job satisfaction, job satisfaction has an effect on employee performance, job satisfaction acts as a mediator between the work environment and performance, job satisfaction has not been proven to mediate the work environment on employee performance, job satisfaction has been proven to mediate career development on employee performance, job satisfaction is not proven to mediate competency on employee performance